Chalcogenide nanoparticles and organic photosensitizers for synergetic antimicrobial photodynamic therapy. Issue 31 (30th July 2021) - Garin, Carlos; Alejo, Teresa; Perez-Laguna, Vanesa; Prieto, Martin; Mendoza, Gracia; Arruebo, Manuel; Sebastian, Victor; Rezusta, Antonio
Abstract : Synergistic antimicrobial effects were observed for copper sulfide (CuS) nanoparticles together with indocyanine green (ICG) in the elimination of wild type pathogenic bacteria ( Staphylococcus aureus ATCC 29213 and Pseudomonas aeruginosa ATCC 27853) and also opportunistic fungal infective yeast ( Candida albicans ATCC 10231). Abstract : Synergistic antimicrobial effects were observed for copper sulfide (CuS) nanoparticles together with indocyanine green (ICG) in the elimination of wild type pathogenic bacteria ( Staphylococcus aureus ATCC 29213 and Pseudomonas aeruginosa ATCC 27853) and also opportunistic fungal infective yeast ( Candida albicans ATCC 10231). Furthermore, large antibacterial effects were observed for clinical isolates of Methicillin-resistant S. aureus (MRSA) PFGE strain-type USA300. This efficient antimicrobial action was attributed to the combined extra- and intracellular generation of reactive oxygen species upon light irradiation. Instead of the use of visible-light for the activation of common photosensitizers, both ICG and CuS nanoparticles can be activated in the near infrared (NIR)-region of the electromagnetic spectrum and therefore, superior tissue penetration would be expected in a potential elimination of pathogenic microorganisms not only on the skin but also in the soft tissue. In the different bacteria studied a 3-log reduction in the bacterial counts was achieved after only 6 min of NIR irradiation and treatment with ICG or CuS alone at concentrations of 40 and 160 µg mL −1, respectively. A maximum bactericidal effect against S. aureus and USA300 strains was obtained for the combination of both photosensitizers at the same concentration. Regarding P. aeruginosa, a 4-log reduction in the CFU was observed for the combination of CuS and ICG at various concentrations. In Candida albicans the combination of both ICG and CuS and light irradiation showed an antimicrobial dose-dependent effect with the reduction of at least 3-log in the cell counts for the combination of ICG + CuS at reduced concentrations. The observed antimicrobial effect was solely attributed to a photodynamic effect and any photothermal effect was avoided to discard any potential thermal injury in a potential clinical application. The generation of reactive oxygen species upon near infrared-light irradiation for those photosensitizers used was measured either alone or in combination. The cytocompatibility of the proposed materials at the doses used in photodynamic therapy was also demonstrated in human dermal fibroblasts and keratinocytes by cell culturing and flow cytometry studies.